A bioabsorbable mechanoelectric fiber as electrical stimulation suture - Sun, Zhouquan; Jin, Yuefan; Luo, Jiabei; Li, Linpeng; Ding, Yue; Luo, Yu; Qi, Yan; Li, Yaogang; Zhang, Qinghong; Li, Kerui; Shi, Haibo; Yin, Shankai; et al. (Nature communications, 2024)
In surgical medicine, suturing is the standard treatment for large incisions, yet traditional sutures are limited in functionality. Electrical stimulation is a non-pharmacological therapy that promotes wound healing. In this context, we designed a passive and biodegradable mechanoelectric suture. The suture consists of multi-layer coaxial structure composed of (poly(lactic-co-glycolic acid), polycaprolactone) and magnesium to allow safe degradation. In addition to the excellent mechanical properties, the mechanoelectrical nature of the suture grants the generation of electric fields in response to movement and stretching. This is shown to speed up wound healing by 50% and reduce the risk of infection. This work presents an evolution of the conventional wound closure procedures, using a safe and degradable device ready to be translated into clinical practice. Sutures are ubiquitous in clinical practice. They close wounds and speed up repair. Here the authors show electroactive sutures, made of triboelectric materials. They generate an electric field in response to natural movement that speed up wound healing by more than 50%